THE IMPACT OF WEBSITE DESIGN ON CUSTOMER SATISFACTION AND PURCHASE INTENTION - TOMIĆ, Tamara; LAVRNIĆ, Igor; VIDUKA, Dejan (Journal of process management and new technologies, 2025)
As e-commerce continues to grow, businesses are realizing the significance of having a strong online presence through well-designed websites. This study aims to establish a comprehensive understanding of the key factors that contribute to website quality and their importance from the consumer's perspective. The main objectives of this research are to identify and prioritize these factors. To achieve this, a questionnaire was distributed among a younger demographic, and participants were asked to rate the importance of 11 parameters related to website quality. The data collected from the survey were analyzed using various statistical tests, including descriptive statistics, Chi-square independence test, and factor analysis. These tests were employed to rank the parameters, examine the influence of gender on respondents' answers, identify areas of disagreement among participants, and determine if certain parameters could be grouped together. The quality of a web page is greatly influenced by various features, including its layout, visual complexity, colorfulness, user-friendliness, speed of processing visitor requests, and reliability. To analyze these features, a feature vector was created. Conducted as exploratory descriptive research, this study utilized a survey to gather data from 117 participants across different social networks. The research encompasses both qualitative and quantitative stages. The qualitative phase aims to identify variables that impact consumer engagement in social commerce, while the quantitative phase involves data collection, validation, and analysis.
Keywords: Website; quality of service; user experience; e-commerce.